2021
DOI: 10.3390/membranes11050325
|View full text |Cite
|
Sign up to set email alerts
|

Membranes for Water, Gas and Ion Separation

Abstract: In recent years, many industry sectors have recognised the importance of sustainable energy, reducing energy consumption and efficient production [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Higher temperature intensities on the draw side led to an increase in water productivity if the current density was maintained at 5 A/m 2 . It was concluded that electro-thermal effects increased the probability of wastewater and brine reuse [101].…”
Section: Forward Osmosismentioning
confidence: 99%
“…Higher temperature intensities on the draw side led to an increase in water productivity if the current density was maintained at 5 A/m 2 . It was concluded that electro-thermal effects increased the probability of wastewater and brine reuse [101].…”
Section: Forward Osmosismentioning
confidence: 99%
“…Industrial discharges and effluents account for approximately 70% of total environmental pollution [ 1 ]. With increasing environmental awareness and energy conservation, treatment of wastewater and exhaust gases from the industrial process is necessary [ 2 ]. Conventional gas separation technologies such as cryogenic distillation, pressure swing adsorption and activated sludge systems have been established to purify gases and wastewater, respectively [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%